Analisa Perbandingan Neraca Untuk Mengukur Kinerja Keuangan Di Kopdit Tuke Ler Cabang Hewokloang - Elisabeth Osi Nofrita Dua Hanes; Yosefina Andia Dekrita; Maria Silvana Mariabel Carcia (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aimed to determine the financial performance at Tuke Ler Hewokloang Credit Union using the horizontal (dynamic) analysis method; namely percentages and ratios. The sample in this research was the balance sheet report of Tuke Ler Hewokloang Credit Union for 2017-2021. The type of data was quantitative data. Data collection was carried out through documentation and interview methods. The data sources used primary and secondary data, primary data in the form of the credit union's history and secondary data in the form of balance sheet reports of Tuke Ler Hewokloang Credit Union. The results showed that the financial performance of Tuke Ler Hewokloang Credit Union in the 2017-2021 period used the percentage and ratio method was comparison based on the rupiah, percentage and ratio showed that total current assets, fixed assets, total assets, equity and capital, and total debt in 2017-2021 tended to increase. It means that the financial performance of Tuke Ler Hewokloang Credit Union on the elements of current assets, fixed assets, total assets, equity capital, and total debt were in good condition and total liabilities in 2017-2021 tended to decrease. It means that the financial performance of Tuke Ler Hewokloang Credit Union on the element of total equity capital was in poor condition.